EFFECT OF FREEZE DRYING PROCESS FOR RETAINING PHYSICAL CHARACTERISTICS OF ORCHID FLOWER - M. SIREESHA (The Journal of Research ANGRAU, 2016)
Flowers are a means of expression, their fragrance and colour brings a sense of freshness and beauty and plays a significant role in human life. In order to protect the inherent qualities of orchid flower through freeze drying technique this study was taken up to polymer pre and post treatments to provide shatter and water resistance, durability, antioxidants, colour setting agents and ultra-violet inhibitors explore the impact of post treatments which protects the flowers from environmental damage. Different preservatives were identified and tested for hydration, pre and post treatments to retain the physical characteristics of flowers. Among the different methods, the flower treated with preservative(a blend of Sprite and Bleach) in luke warm water(43-45oc) during hydration process, followed by pre-treatment with Base composition III and post treatment by application of Dried Material Preservative (DMP) as sealant as post treatment was found to be effective for retaining inherent qualities of the flowers.